A New Ramesside Copy of the Teaching of Amenemhat: The Hieratic Ostracon from Abydos - Navratilova, Hana.
A newly excavated ostracon from Abydos bearing the concluding chapter of “The Instruction (a.k.a. Teaching) of King Amenemhat” opens up an interesting enquiry. An ostracon found in the immediate vicinity of a New Kingdom royal memorial temple and carrying an excerpt from a major literary text is an important find, as it develops our insight into New Kingdom educational practices and intellectual quests. The range of ostraca types and text genres appearing in the area of the temple of Ramesses II points to a fully functional temple organization with a building phase and an operational phase, with supplies and literate personnel on site, potentially in different administrative roles. Studies in educational and intellectual pursuits, in turn, are key to expanding our comprehension of the functions—and enjoyment—of Egyptian culture.